(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The study aimed to identify the extent of graduate students’ use of Wiki Data sources and references in the humanities departments (Archaeology, History, Geography, Sociology, Philosophy, and Library and Information Science) at the Faculty of Arts and Humanities, Damascus University, over the past six years (2018–2023). The investigation was based on three primary variables: specialization, academic degree, and time span. The focus was directed toward intellectual output represented by master’s theses and doctoral dissertations. The bibliometric method was employed to analyze the data, specifically through a direct examination of 466 academic theses and dissertations within these departments. A direct citation count technique, a type of bibliometric analysis, was utilized. The study found that while some theses employed references from Wiki Data, the majority (85.15%) did not. This suggests a high level of awareness among researchers in the selected specializations regarding the scientific selection of information. The study also highlighted the positive or negative impact of each academic thesis on the final outcomes of the department, the faculty, and ultimately the university as a whole. The researcher proposed that the Scientific Research Directorate at Damascus University should establish a specific criteria for utilizing Wiki Data sites in scientific research. These criteria should include: The completeness of the bibliographic data for the source, Attribution to a responsible organization or official entity (such as unions or authorities), the quality and relevance of the content, ensuring it is not available from a more reliable source, evaluation and review of the data on the site, with strict supervision of edits, additions, and deletions, the currency of the information provided.